Internet Addiction and Its Associated Factors Among African High School and University Students: Systematic Review and Meta-Analysis - Zewde, Edgeit Abebe; Tolossa, Tadesse; Tiruneh, Sofonyas Abebaw; Azanaw, Melkalem Mamuye; Yitbarek, Getachew Yideg; Admasu, Fitalew Tadele; Ayehu, Gashaw Walle; Amare, Tadeg Jemere; Abebe, Endeshaw Chekol; Muche, Zelalem Tilahun; Fentie, Tigabnesh Assfaw; Zemene, Melkamu Aderajew; et al. (Frontiers in Psychology, 2022)
Introduction: Internet addiction is characterized by excessive and uncontrolled use of the internet affecting everyday life. Adolescents are the primary risk group for internet addiction. Data on internet addiction is lacking in Africa. Thus, this review aimed to determine the pooled prevalence of internet addiction and its associated factors among high school and university students in Africa. Methods: A comprehensive literature search was conducted using electronic databases (PubMed/MEDLINE, Web of science, Hinari, and Google scholar) to locate potential studies. Heterogeneity between studies was checked using Cochrane Q test statistics and I2 test statistics and small-study effects were checked using Egger’s statistical test at a 5% significance level. A sensitivity analysis was performed. A random-effects model was employed to estimate the pooled prevalence and associated factors of internet addiction among students. The primary outcome of measure of this review was the prevalence of internet addiction and the secondary outcome of measures are the factors associated with internet addiction. Results: A total of 5562 studies were identified among the five databases. Of these, 28 studies from 10 countries with 14,946 high school and university students were included in this review. The overall pooled prevalence of internet addiction among the students was 34.53% (95% Confidence Interval (CI): 26.83, 42.23, I2 = 99.20%). Male sex (Pooled Odds Ratio (POR) = 1.92, 95% CI:1.43, 2.57 I2 =0.00), urban residence (POR = 2.32, 95% CI:1.19, 4.53, I2 = 59.39%), and duration of daily internet use for more than four hours (POR= 2.25, 95% CI:1.20, 4.21, I2 = 0.00%, were significantly associated with internet addiction among adolescents. Conclusion Almost one-third of university and high school students in Africa are addicted to the internet. Male students, those from urban areas, and those who use the internet for more than 4 hours per day have higher odds of internet addiction. Thus, we recommend that health planners and policymakers pay attention to the use of the internet and internet addiction in Africa. addiction in Africa.